Reatividade das nanopartículas de dióxido de titânio com a superfície modificada por grupos peróxo - Francatto, Patrícia (2016)
The welfare of the human population depends of the technological and scientific development. However, this model of economic growth has generated a huge ecological impact. For this reason, it is necessary new and more efficient processes and methods of synthesis to sage energy. This study employed a new approach of the "The Oxidant PeroxoMethod" (OPM) to obtain highly reactive nanoparticles of titanium dioxide (TiO2) with the surface modified with peroxide groups (TiO2 -OPM). We synthesized these TiO2-OPM using titanium metal and titanium isopropoxide as titanium source and to evaluate the reactivity of these precursors, two different composition of bismuth titanates (the selenita Bi12TiO20 and the perovskite Bi4Ti3O12 phases) were synthesized by means of the conventional solid-state reaction. These materials were characterized using differential scanning calorimetry (DSC), thermogravimetric analysis (TG), X-ray diffraction (XRD), Raman spectroscopy and scanning eléctron (SEM) and transmission eléctron (TEM) microscopies. We observed that both TiO2-OPM precursors are identical reagarding their reactivity and structure, with the advantage that the material synthesized from the alcooxide is easier, cheaper and faster that the material obtained from titanium metal. Moreover, we could observe that the peroxide groups on the surface of the nanoparticles were resposable by the reactivity of these nanoparticles, as observed by the lower temperatures used to obtain single phase bismuth titanates with different composition.